The Influence of Bankruptcy Prediction Using the Altman Z Score Modified Approach to Stock Prices (Survey of Private Companies in the General Banking Sector in the Indonesia Stock Exchange in 2015 - 2018) - et. al., Tetty Lasniroha Sarumpaet, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was conducted with the aim to determine the effect of the Altman Z Score and the variables in it namely Working Capital to Total Assets, Retained Earnings to Total Assets, Earnings Before Interest and Tax and Market Value Equity to Book Value of Debt on stock prices in private sector companies general banking listed on the Indonesia Stock Exchange in 2015 - 2018. Factors tested in this study are the Altman Z Score and the variables in it namely the Working Capital to Total Assets ratio, Retained Earnings to Total Assets, Earnings Before Interest and Tax, and Market Value Equity to Book Value of Debt as the independent variable and stock price as the dependent variable. This research method is descriptive and verification. The population in this study is private sector banking sector private companies listed on the Indonesia Stock Exchange in 2015 - 2018, amounting to 45.